Stevens Johnson syndrome during postoperative period. A case report. (August 2017) - Peinado, Begoña; Álvarez, Estibaliz; Verón, Ana; Castell, Jose; Acevedo, Anais; Guevara, Jenny; Ayuela, Susana; Mata, Alberto; Díaz Domínguez, Joaquín
Abstract : Introduction: The Stevens Johnson syndrome is a rare and potentially fatal cutaneous reaction to medicaments or infections. The most common drugs linked to this syndrome are antibiotics (such as sulfonamides, cephalosporines and quinolones), anticonvulsivant drugs (carbamazepine, phenytoin) and nonsteroidal anti-inflammatory drugs (NSAIDs). It is characterized by extensive necrosis with detachment of the epidermis, and the mortality rate rises up to 30%. We present a case of Stevens Johnson syndrome associated with drugs administration during postoperative period. Case description: A 73-year-old female reported to Department of Hepatic Surgery for a hepatectomy due to colorectal liver metastases. Her oncological history initiated 5 months ago with a colorectal obstructive tumor and liver metastases in both lobes. An emergency Hartmann procedure was performed following adjuvant chemotherapy, with good response. The surgical team decided to perform a two stage hepatectomy. The postoperative period was torpid and a reintervention for bowel obstruction was required, as well as two long stays in the Intensive Care Unit. A month after the first surgery, the patient presented with a reddish maculopapular lesion on the neck that rapidly extended to the back and forearms. An intra-oral erythema and conjunctival ulcerations were also noted. The diagnosis of syndrome was confirmed by the Department of Dermatology with a skin biopsy. Pharmacology and Allergy Departments completed the study and proposed that the syndrome was possibly due to peniciline and NSAIDs. Despite the efforts of the multidisciplinary team, the supportive care, and the early retreat of the possible causing drugs and ciclosporine plus corticosteroids treatment, the patient presented with severe liver failure and finally died after 2 months of hospitalization. Conclusions: Cutaneous reactions are a very common condition during the postoperative period, most of them are related to habitual drugs regimens. Considering this, it is of paramount importance to keep in mind that the Stevens Johnson syndrome is a rare but severe dermatological pathology in which early diagnosis and treatment is vital.